Update Breast Cancer 2021 Part 3 – Current Developments in the Treatment of Early Breast Cancer: Review and Assessment of Specialised Treatment Scenarios by an International Expert Panel - Fehm, Tanja N.; Stickeler, Elmar; Fasching, Peter A.; Janni, Wolfgang; Kolberg-Liedtke, Cornelia; Kolberg, Hans-Christian; Lüftner, Diana; Müller, Volkmar; Schütz, Florian; Thomssen, Christoph; Belleville, Erik; Behrens, Annika; Bader, Simon; Untch, Michael; Welslau, Manfred; Würstlein, Rachel; Thill, Marc; Krug, David; Hartkopf, Andreas D. (Geburtshilfe und Frauenheilkunde, 2021)
The continuous availability of findings from new studies repeatedly results in updated treatment recommendations and guidelines. In the case of breast carcinoma in particular, several studies have been published in the last few years that have transformed how early and advanced breast carcinoma is being treated. However, this by no means means implies that there is agreement among all experts on specific issues. It is precisely the diversity of interpretation of guidelines and study findings that reflects the constantly changing available data and its complexity, as well as the availability of new drugs. In recent years, new substances such as pertuzumab, T-DM1, neratinib and capecitabine have become available to treat patients with early stages of breast carcinoma. Furthermore, the first results on the use of CDK4/6 inhibitors for adjuvant treatment have now been published. Last but not least, the use of multigene tests to avoid the necessity of chemotherapy in certain patients is still under discussion. This review summarises the state of the data and publishes the results of the survey completed by experts at the 2021 St. Gallen Breast Cancer Conference on early-stage breast cancer.Kontinuierlich neue Studienergebnisse führen wiederholt zu aktualisierten Therapieempfehlungen und Leitlinien. Insbesondere beim Mammakarzinom wurden in den letzten Jahren einige Studien veröffentlicht, welche die Behandlung des frühen und fortgeschrittenen Mammakarzinoms deutlich verändert haben. Dies bedeutet jedoch nicht, dass die Meinungen aller Experten bei speziellen Fragen übereinstimmen. Gerade die Diversität bezüglich der Interpretation der Leitlinien und Studienergebnisse reflektiert die sich ständig ändernde Datenlage und ihre Komplexität sowie die Verfügbarkeit von neuen Medikamenten. Für die Therapie von Patientinnen mit frühen Stadien des Mammakarzinoms sind in den letzten Jahren neue Substanzen wie Pertuzumab, T-DM1, Neratinib, Capecitabin und weitere hinzugekommen. Des Weiteren gibt es erste Ergebnisse zum Einsatz von CDK4/6-Inhibitoren in der adjuvanten Situation. Nicht zuletzt wird nach wie vor diskutiert, wie Multigentests eingesetzt werden können, um den Einsatz von Chemotherapien bei bestimmten Patientinnen vermeiden zu können. Diese Übersichtsarbeit fasst den Datenstand zusammen und veröffentlicht die Abstimmungsergebnisse der St.-Gallen-Brustkrebskonferenz 2021 zum Mammakarzinom in frühen Krankheitsstadien.
Keywords: early breast cancer; therapy decisions; expert panel